Putting people first : Sociological variables in Rural development - Cernea, Michael M. (ed.) (New York, 1991)
Incorporating information about projects assisted by the World Bank, this book includes studies of the social organization of productive systems, the typology of development projects, and stages in the project cycle.
Keywords: Agriculture development projects Social aspects